2021
DOI: 10.1016/j.gore.2021.100840
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib plus pembrolizumab in patients with advanced or recurrent uterine carcinosarcoma

Abstract: Highlights No partial or complete responses to pembrolizumab and lenvatinib therapy were observed in advanced or recurrent UCS. Median PFS and OS following pembrolizumab and lenvatinib therapy is similar to traditional cytotoxic regimens. Pembrolizumab and lenvatinib therapy was only used in patients who had failed two or more lines of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The ORR for the 20 patients was 60.0%, and 2 of 6 patients with UCS exhibited a response. An initial small retrospective case series by Hunt et al [24] that included 7 UCS patients with UCS treated with LEN/PEM found no partial or complete response. However, that study did not include patients who had received only one line of prior therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The ORR for the 20 patients was 60.0%, and 2 of 6 patients with UCS exhibited a response. An initial small retrospective case series by Hunt et al [24] that included 7 UCS patients with UCS treated with LEN/PEM found no partial or complete response. However, that study did not include patients who had received only one line of prior therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no UCS was included in KEYNOTE-775. Hunt et al presented a small retrospective series with pembrolizumab and lenvatinib in seven patients of advanced or recurrent UCS as ≥ third-line, which observed no partial or complete response [ 40 ], while it was unknown if used earlier at first relapse. A ROCSAN trial with an anti-PD1 (dostarlimab) and a PARPi (niraparib) is now recruiting [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, around 10% of endometrial carcinosarcomas are MSI-H, ~5% are POLE mutated, and~60% show PD-1/PD-L1 immunohistochemical expression; immunotherapy (alone or in combination with tyrosine kinase inihibitor) may be particularly promising in these molecular subgroups 3 4 21–27. Nevertheless, to date, only anecdotal evidence exists 108 109…”
Section: Novel Therapeutic Agents and Future Perspectivesmentioning
confidence: 99%
“…108 109 A small retrospective series including seven patients (14% MSI-H/MMRd) tested the efficacy of the pembrolizumab/lenvatinib doublet in endometrial carcinosarcoma and showed no partial or complete responses. 109 One case report described a partial response with pembrolizumab used in a heavily pretreated patient with POLE mutated endometrial carcinosarcoma. 110 Another case of a patient with platinum-refractory, PD-L1-positive, MSI-H endometrial carcinosarcoma is described.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%